The Atlantic Slave Trade from Angola: A Port-by-Port Estimate of Slaves Embarked, 1701–1867 - da Silva, Daniel B. Domingues (The International journal of African historical studies, 2013)
[...]for the periods when these series match, Klein's figures for slaves leaving Luanda are four percent higher than Goulart's and half percent lower than Birmingham's, while for Benguela his numbers are two percent higher than Goulart's and one percent higher than Birmingham's. [...]the trade from Angola expanded continuously from the eighteenth to the midnineteenth centuries with captives embarked from several ports along the coast of Angola.